2009
DOI: 10.1063/1.3086320
|View full text |Cite
|
Sign up to set email alerts
|

Swimming speeds of filaments in nonlinearly viscoelastic fluids

Abstract: Many micro-organisms swim through gels and non-Newtonian fluids in their natural environments. In this paper, we focus on micro-organisms which use flagella for propulsion. We address how swimming velocities are affected in nonlinearly viscoelastic fluids by examining the problem of an infinitely long cylinder with arbitrary beating motion in the Oldroyd-B fluid. We solve for the swimming velocity in the limit in which deflections of the cylinder from its straight configuration are small relative to the radius… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
155
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 31 publications
9
155
1
Order By: Relevance
“…The importance of elastic effects are quantified by the Deborah number De, defined as the ratio of the relaxation time τ of the fluid to the characteristic time scale of the swimmer. For an infinite sheet or filament deformed by low-amplitude traveling waves and suspended in a dilute polymer solution described by the Oldroyd-B model, the swimming speed is always less than the Newtonian speed and decreases with increasing Deborah number (7)(8)(9). These theoretical predictions agree roughly with the measurements of swimming C. elegans (6).…”
supporting
confidence: 80%
“…The importance of elastic effects are quantified by the Deborah number De, defined as the ratio of the relaxation time τ of the fluid to the characteristic time scale of the swimmer. For an infinite sheet or filament deformed by low-amplitude traveling waves and suspended in a dilute polymer solution described by the Oldroyd-B model, the swimming speed is always less than the Newtonian speed and decreases with increasing Deborah number (7)(8)(9). These theoretical predictions agree roughly with the measurements of swimming C. elegans (6).…”
supporting
confidence: 80%
“…There, it was shown that, for fixed swimming kinematics, the swimming speed for the swimming sheet systematically decreases compared to the Newtonian case for all Oldroyd-type fluids to leading order in smallamplitude waveforms. Subsequently the same result was obtained for planar undulating filaments [33] and helical waves [34] in Oldroyd-B fluids.…”
Section: Infinite Modelssupporting
confidence: 60%
“…In contrast, prior asymptotic analysis by Fu et al [34] showed that, like the swimming sheet, the leading-order swimming speed (in a small-amplitude perturbation series) of a body propagating helical waves in an Oldroyd-B fluid is always slower than in a non-Newtonian fluid. This discrepancy between the small-amplitude asymptotics and large-amplitude experiments was resolved in numerical work by Spagnolie et al for a helix in an Oldroyd-B fluid [37].…”
Section: B Large-amplitude Deformationsmentioning
confidence: 58%
See 1 more Smart Citation
“…One exception is the literature on swimmers wherein models have been developed for a single organism or a few organisms that propel themselves in viscous [48][49][50][51][52][53][54][55][56][57][58] and non-Newtonian fluids [57,[59][60][61][62][63][64][65][66][67]. In particular, swarming hydrodynamic theories have been derived wherein swimmer densities with or without fluid flows are described as continuous fields [4,19,68,69].…”
mentioning
confidence: 99%